Saberes ancestrales de la Cultura Waranga y el turismo medicinal en el cantón Guaranda, año 2019 - Castro Triana, Karol Mabel (2019)
The current research is based on the Ancestral Knowledge and Medicinal Tourism of the Waranga Culture, Bolívar Province nestled on the flanks of the Ecuadorian highlands and how these knowledge, traditions and knowledge they would contribute to the medicinal and experiential tourism development of the Guaranda Canton, with the objective of strengthening their cultural identity through the preservation, recognition and dissemination of their heritage wisdom, encouraging the population to take advantage of their ancestral and experiential knowledge about Natural Medicine that over time, space and worldview are being forgotten by the new generations. With the rise of globalization, the advancement of technology and the acculturation process in some members of the Waranga community, they have adopted different cultural habits giving way to Cultural Syncretism causing the process of self-determination of cultural identity of this ethnic group. Through the use of methods, techniques and instruments, it was acquired as a result that the limited knowledge about Ancestral Knowledge and the scarce practice of Natural Medicine of the Waranga Culture, It is due to the decline of cultural identity, causing the disuse of the medicinal plants that the Yachaks and midwives possess for the cure of diseases, and prefer to make use of Western medicine. Ancestral knowledge is traditional manifestations, experiences, events inherited by ancestors that are based mainly on the wisdom and practice of customs, traditions, historical events, rituals, myths and legends, elements that are considered as the most important part of a town and its inhabitants becoming a main piece of its Cultural Identity, through these inheritances that the ancestors have left to these communities through the development of Cultural Tourism and Medicinal Tourism, it will allow to increase economic income and social integration to the communities that do it, contributing to improve the quality of life of its inhabitants